Central American Novel about the Migrant: Las murallas and Al otro lado del San Juan - Camacho Guzmán, Gustavo (2020)
Two Central American novels with a migrant as protagonist are analyzed: Las murallas, by Adolfo Méndez Vides, and Al otro lado del San Juan, by Petronio Marcenaro Romero. Uprooting, marginalization and discrimination are emphasized in both novels. In the former, the characters are never able to leave their precarious lives, while in the latter xenophobia and the oppression of migrants prevail, within the framework of an imminent war between Costa Rica and Nicaragua.